2021
DOI: 10.22541/au.161994432.24828107/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lateral flow assays for the detection of African swine fever virus antigen are not fit for field diagnosis of wild boar carcasses

Abstract: African swine fever (ASF) is one of the most important viral diseases of domestic pigs and wild boar. Apart from endemic cycles in Africa, ASF is now continuously spreading in Europe and Asia. As ASF leads to severe but unspecific clinical signs and high lethality, early pathogen detection is of utmost importance. Recently, “point-of-care” (POC) tests have been intensively discussed for the use in remote areas but also in the context of on-farm epidemiological investigations and wild boar carcass screening. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…These field results are in line with experimental studies (Pikalo et al., 2021). A recent study found a high positivity rate for Ag‐LFD during the acute phase of disease between days 4 and 7 post‐infection (dpi) when testing EDTA‐blood as sample matrix or up to 10 days when serum is used as the sample matrix (Deutschmann et al., 2022; Pikalo et al., 2021). Therefore, it should be kept in mind that the sensitivity of Ag‐LFD limits its use to acutely sick animals 4–10 dpi.…”
Section: Discussionmentioning
confidence: 99%
“…These field results are in line with experimental studies (Pikalo et al., 2021). A recent study found a high positivity rate for Ag‐LFD during the acute phase of disease between days 4 and 7 post‐infection (dpi) when testing EDTA‐blood as sample matrix or up to 10 days when serum is used as the sample matrix (Deutschmann et al., 2022; Pikalo et al., 2021). Therefore, it should be kept in mind that the sensitivity of Ag‐LFD limits its use to acutely sick animals 4–10 dpi.…”
Section: Discussionmentioning
confidence: 99%